Determination of Magnetic Mineral Crystal Structure Using X-Ray Diffraction (XRD) on Igneous Rock from Ogolowe and Bajugan Village, Toli toli District Central Sulawesi - Musfirah Cahya Fajrah; Alia Mapesso; Sandra Kasim (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2017)
Study of igneous rocks derived from Ogowele Village and Village Toli-Toli Bajugan has been conducted to determine the magnetic minerals contained in the igneous rocks, as well as determine the crystal system, lattice constants and field diffraction by comparison sieve 60 mesh and 80 mesh. Process characterization and analysis using X-Ray Diffraction (XRD). Characterization and analysis of the results showed that the compound was detected both rock samples Fe3O4, SiO2, Al2O3 and MnO2. Igneous rocks derived from Ogowele village is dominated by compounds SiO2 (quartz) by 52% and rocks from Bajugan village dominated by the compound Fe3O4 (magnetite) by 40%. The crystal structure is cubic and hexagonal compound to compound Fe3O4 SiO2. Fe3O4compound cubic lattice constants are a = b = c is 8.375 Å. To compound the hexagonal SiO2 ie a = b of 4.898 Å and c of 5.385 Å. Field diffraction on Fe3O4compound is (3 1 1) and the SiO2 compound that is (1 0 1).Keywords: X-Ray Diffraction, Fe3O4 Compound, SiO2 Compound, cubic, hexagonal